Polymorphisms of two histamine-metabolizing enzymes genes and childhood allergic asthma: a case control study - Szczepankiewicz, Aleksandra (BioMed Central, 2010)
BACKGROUND: Histamine-metabolizing enzymes (N-methyltransferase and amiloride binding protein 1) are responsible for histamine degradation, a biogenic amine involved in allergic inflammation. Genetic variants of HNMT and ABP1 genes were found to be associated with altered enzyme activity. We hypothesized that alleles leading to decreased enzyme activity and, therefore, decreased inactivation of histamine may be responsible for altered susceptibility to asthma. METHODS: The aim of this study was to analyze polymorphisms within the HNMT and ABP1 genes in the group of 149 asthmatic children and in the group of 156 healthy children. The genetic analysis involved four polymorphisms of the HNMT gene: rs2071048 (-1637T/C), rs11569723 (-411C/T), rs1801105 (Thr105Ile = 314C/T) and rs1050891 (1097A/T) and rs1049793 (His645Asp) polymorphism for ABP1 gene. Genotyping was performed with use of PCR-RFLP. Statistical analysis was performed using Statistica software; linkage disequilibrium analysis was done with use of Haploview software. RESULTS: We found an association of TT genotype and T allele of Thr105Ile polymorphism of HNMT gene with asthma. For other polymorphisms for HNMT and ABP1 genes, we have not observed relationship with asthma although the statistical power for some SNPs might not have been sufficient to detect an association. In linkage disequilibrium analysis, moderate linkage was found between -1637C/T and -411C/T polymorphisms of HNMT gene. However, no significant differences in haplotype frequencies were found between the group of the patients and the control group. CONCLUSIONS: Our results indicate modifying influence of histamine N-methyltransferase functional polymorphism on the risk of asthma. The other HNMT polymorphisms and ABP1 functional polymorphism seem unlikely to affect the risk of asthma.